Effectiveness of an Anger Intervention for Military Members with PTSD: A Clinical Case Series. Issue 9 (23rd March 2018) - Cash, Richard; Varker, Tracey; McHugh, Tony; Metcalf, Olivia; Howard, Alexandra; Lloyd, Delyth; Costello, Jacqueline; Said, David; Forbes, David
Abstract: Objective: Problematic anger is a significant clinical issue in military personnel, and is further complicated by comorbid post-traumatic stress disorder (PTSD). Despite increasing numbers of military personnel returning from deployment with anger and aggression difficulties, the treatment of problematic anger has received scant attention. There are currently no interventions that directly target problematic anger in the context of military-related PTSD. The aim of this case series is to examine the effectiveness of an intervention specifically developed for treating problematic anger in current serving military personnel with comorbid PTSD. Methods: Eight Australian Defence Force Army personnel with problematic anger and comorbid PTSD received a manualized 12-session cognitive behaviorally based anger intervention, delivered one-to-one by Australian Defence Force mental health clinicians. Standardized measures of anger, PTSD, depression, and anxiety were administered pre- and post-treatment. Results: The initial mean severity scores for anger indicated a high degree of pre-treatment problematic anger. Anger scores reduced significantly from pre to post-treatment ( d = 1.56), with 88% of participants exhibiting meaningful reduction in anger scores. PTSD symptoms also reduced significantly ( d = 0.96), with 63% of participants experiencing a clinically meaningful reduction in PTSD scores. All of those who took part in the therapy completed all therapy sessions. Conclusions: This brief report provides preliminary evidence that an intervention for problematic anger not only significantly reduces anger levels in military personnel, but can also significantly reduce PTSD symptoms. Given that anger can interfere with PTSD treatment outcomes, prioritizing anger treatment may improve the effectiveness of PTSD interventions.